Physical planning and growth of private primary schools in Kenya - Njiri, Julius; Mbugua, Levi; Kiambati, Kellen; Mwenja, Dominic (Journal of Management and Business Education, 2020)
In Kenya, the number of private schools has increased more than four times since the introduction of the Free Primary Education (FPE) policy in 2003. The number of children attending private primary schools increased from 4.6% in 2004 to 11.5% in 2007. With such increment, there has been challenges on the determinants of growth of education institutions. It is against this background that the study examined the influence of physical planning on the growth of private primary schools in Kenya. the study was anchored in the resource dependency view where the managers of institutions have the ability to acquire, Plan and maintain resources that are important to the growth of an organization. The target population in this study comprised of 7,418 private primary schools in all eight regions of Kenya. Cluster sampling technique was employed of 50% of the target regions were sampled, leading to four out of eight regions being selected. From these regions random sampling was then used to select 320 respondents who were either the principals’/Head teachers or deputy principal of the schools. A questionnaire was used to collect data and Structural Equation Modeling was used to analyse data. The study found a strong and significant correlation between physical planning and growth of primary schools. This study therefore recommended that physical planning was an important factor in determining growth of private schools. The study further recommends that owners of private primary schools should be aware of the facilities that are crucial and most important to students in the teaching and learning. This will intern influence the growth of the private primary schools in Kenya.